Internalization of Tasamuh Values in PAI Learning Using Contextual Teaching - Hairani, Reskina Cahaya Mulia; Tanjung, Ellisa Fitri Tanjung Fitri; -, Nurzannah (Universitas Negeri Makassar, 2025)
ABSTRACTThis study aims to analyze the internalization of tasamuh value in Islamic Religious Education (PAI) learning by using Contextual Teaching and Learning (CTL) model at SMPN 3 Siempatnempu. This study used a qualitative approach with descriptive analytical methods and involved informants from students, PAI teachers, principals, and student guardians. Data was collected through observation, interview, and documentation study. The results of this study concluded that first, the fostering of tasamuh attitude that has been implemented in SMPN 3 Siempatnempu is that students accept other religious adherents who become one of their communities in the classroom, respect other religious adherents and are patient with the differences that exist in their respective beliefs. Second, students' behavior in respecting the implementation of worship of other religions, not denouncing or abusing the worship of other religions, being roomy in accepting every difference and not imposing their own will, getting along with all friends without distinguishing their religion, giving non-Muslim friends the opportunity to pray according to their respective religions, providing security to other people who are worshiping, holding friendships with friends of different religions, helping friends of different religions who are in trouble.Keywords: Contextual Teaching and Learning, Islamic Religious Education, Tasamuh.